Analisis Beban Kerja Mental Pada Karyawan Air Minum Dalam Kemasan “Ajibpol” Menggunakan Metode NASA-TLX - Arta, Zia Dwi; Satriyo, Dony; Apriyadi, Janu (Universitas Muhammadiyah Sorong, 2025)
Bottled water in Indonesia continues to grow along with the increasing demand for clean and practical water. Company performance is crucial to maintaining competitiveness, one way of doing this is through optimal workload management. Workload, both physical and mental, is directly related to employee fatigue levels. In measuring mental workload, subjective methods such as NASA-TLX are widely used because they are more economical and representative. The NASA-TLX method measures six dimensions: mental demand, physical demand, time demand, performance, effort level, and frustration level. In the Bottled water studied, problems were found such as frequently not achieving production targets, product labeling errors that are still done manually, bottle damage due to worker negligence when taking from the warehouse to the production area, and there are sudden changes in work systems due to employees suddenly requesting leave and being replaced, these factors causing high workloads. The measurement results showed that the highest mental workload was found in administrative staff, quality control, and operational staff, with average scores of 82, 83, and 85, respectively. Simulations of adding workers showed a significant decrease in mental workload, from the high category to medium or low. This study proves that increasing the workforce can be an effective solution to reduce mental workload and improve employee performance in the AMDK sector.